Congenital Anomalous Origin of Coronary Artery Disease in Children With Syncope: A Case Series - Gao, Yumeng; Zhang, Qingyou; Sun, Yan; Du, Junbao (Frontiers in Pediatrics, 2022)
Objective This study is aimed to analyze the characteristics of congenital anomalous origin of coronary artery in pediatric patients with syncope. Methods A total of eight patients were retrospectively analyzed from August 2018 to August 2020 who were admitted to the Peking University First Hospital with the complaint of syncope and were diagnosed with congenital coronary artery disease. Results Eight patients were included in the study with a median age of 12.5 ±2.7 (8–16) years. Four of them were males, and four were females. Six of the eight patients were diagnosed as right anomalous coronary artery from the opposite sinus (R-ACAOS), while two patients were diagnosed as left anomalous coronary artery from the opposite sinus (L-ACAOS). The most frequent inducement was exercise, and the commonest prodromes were dizziness and blurred vision. Serum cardiac markers and exercise electrocardiography test (EET) were normal in seven of the patients. The majority of cases had abnormal electrocardiograms (ECGs), but only two of them manifested elevated/depressed ST-T segments. Seven patients had positive head-up tilt test (HUT). Echocardiography and coronary artery computed tomography angiography (CTA) were performed to aid the diagnosis. Coronary unroofing procedures were conducted in four patients, and none of them reported syncope after the surgery. The other four patients received routine medical treatment for vasovagal like syncope. Two patients out of them became asymptomatic, and in the other two patients, episodes of syncope were reduced, but they still required medical treatment. Conclusions Congenital coronary artery anomalies in children with syncope need prompt attention. Though ECG and echocardiography are the common methods for investigating cardiac syncope, they have limited ability to find coronary artery anomalies. When coronary artery anomalies are suspected, coronary CTA should be considered.